The development of a metaphoric competence. A didactic proposal of educational innovation - Gutiérrez Pérez, Regina (Innovation in language learning and teaching, 2019)
This article presents a didactic experience carried out in the Degree of Translation and Interpreting (English) at Pablo de Olavide University in Seville and it is part of a project of Innovation and Teaching Development. The main objective is the development in students of a metaphoric competence - metaphorical awareness and strategies to understand metaphors in a L2, since the teaching of idiomatic language is a missing section in textbooks and teaching methodologies in the current university panorama. With this purpose, we show how to learn metaphors and idioms effectively in a foreign language context following the tenets of the Conceptual Metaphor Theory (CMT), a subdiscipline of Cognitive Linguistics (CL), which focuses on the conceptual motivation behind figurative meaning. By analyzing the systematicity and experiential basis of the expressions subject of study, some pedagogical suggestions are provided in order to facilitate the acquisition of idiomatic expressions. The results, analyzed through classroom interaction and practice, a final test, a post-test examination six months later and an anonymous student questionnaire, confirm the undoubted effectiveness of the innovations introduced and, therefore, we advocate the inclusion of figurative language in any L2 syllabus, given that its acquisition contributes to the comprehensive development of a communicative competence.